SOCIAL MEDIA USERS AND THE IMPACT OF SOCIAL MEDIA ON CONSUMER PURCHASE DECISION PROCESS - Kleimola, Minna (My University, 2013)
Social Media has influenced peoples’ lives in many ways. It enables interaction between people and has changed the media landscape from traditional one-way media to two-way interactive media. Social media is international environment and therefore this study contributes research knowledge about chosen subject internationally. The purpose of this study is to investigate the users of social media and the social media impact on consumers buying process. The study attempts to identify the motivations in order to use social media and stages on consumer purchase decisionprocess related to the social media context. The research is based on qualitative approach and the data collection is based on diary reports from 25 participants. Total 707 diary entries of social media activities were received and the findings related are presented in the study. The social media activities, consists of three levels particularly consuming, participation and producing. Most of the activities concerned consuming of content and participation. The data analysis of this thesis confirms three key motivations engaged the activities of social media information, entertainment and socializing. The findings show that the social media influences on, consumer purchase decisionprocess in each stage and indicates that user-generated content plays important role in decision-making. The social Media is a new information search channel that saves time and cuts costs.
Keywords: Social Media; Consumer Behaviour; Purchase decision process; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|